IMPLIKASI YURIDIS TERKAIT PERAN NOTARIS DALAM PENGESAHAN PERJANJIAN PERKAWINAN DI INDONESIA PASCA PUTUSAN MAHKAMAH KONSTITUSI NOMOR 69/PUU-XIII/2015 - Desimawati Sinaga (Fakultas Hukum Universitas Djuanda Bogor, 2020)
Prenuptial Agreement has been changed by the Constitutional Court Decision Number 69/PUU-XIIII/2015. This decision issued toward a suit made by a woman named Ike Farida, who is married to a man with different nationality without making Prenuptial Agreement. This research aims to ascertain the legal standing of Prenuptial Agreement and the authority of Notary in legalizing Prenuptial Agreement after the establishment of Constitutional Court Decision Number 69/PUU-XIIII/2015.This research uses normative legal method through the statute approach and secondary data analysis. This research comprises two phases, there are conducting literature review to learn the regulation of the authority of Notary in legalizing Prenuptial Agreement after the establishment of Constitutional Court Decision Number 69/PUU-XIIII/2015 and various literature. Afterward, researcher established a field research method by interviewing Notary, the Official of Office of Religious Affairs (Kantor Urusan Agama) and the Official of Civil Registry Office (Dinas Kependudukan or Kantor Catatan Sipil).The Constitutional Court Decision Number 69/PUU-XIIII/2015 permits married couple to make Prenuptial Agreement after the marriage ceremony. Additionally, the Agreement may be canceled based on their consent as long as it does not inflict a financial loss to the third party. Subsequently, since the establishment of such Decision, the Legalization of Prenuptial Agreement by Notary is no longer similar to Prenuptial Agreement Legalization established by the Staff of Marriage Registry. The Notary does have authority to make an Authentic Deed concerning Prenuptial Agreement in question, and such Deed will be used for Prenuptial Agreement registration in the Office of Religious Affairs and Civil Registry Office. However, the Deed in question must legalized by the Staff of Marriage Registry hence it binds the third party.Key words: Prenuptial Agreement, Legalization, Notary, The Constitutional Court Decision Number 69/PUU-XIIII/2015.